Persistent Median Artery as an Unusual Finding in the Carpal Tunnel: Its Contribution to the Blood Supply of the Hand and Clinical Significance - Haładaj, Robert (Med Sci Monit, 2019)
BACKGROUND: Knowledge of the variable relation of the persistent median artery (PMA) to the median nerve and its contribution to the formation of the superficial palmar arch is of great clinical significance. This study presents a proposal of specific variables which might be introduced to characterize the PMA in the wrist region. MATERIAL/METHODS: One hundred and twenty-five randomly selected, isolated upper limbs fixed in 10% formalin solution were subjected to anatomical dissection. RESULTS: Of the 125 upper limbs, PMA was found in 5 specimens (4% of the total number of limbs). In the carpal tunnel, the artery occupied the anterolateral position (2 cases), the anterior position (2 cases) or the anteromedial position (1 case) in relation to the median nerve. Two types of superficial palmar arches with significant contributions from the PMA were observed in the studied material: complete medio-ulnar arch and an incomplete arch without a connection between the territories of the ulnar and median arteries. The mean ratio of the diameter of the PMA to the diameter of ulnar artery at the level of the wrist was 0.59 (min.=0.38, max=0.83, SD=0.19). CONCLUSIONS: Orthopedic and hand surgeons should be aware of the probability of occurrence of the PMA in both planning and conducting surgeries within the wrist region and within the carpal tunnel, as this anomalous vessel might present significant contributions to the arterial blood supply of the hand and might potentially play an important role in the presence of notable clinical symptoms and presentations.